Harnessing local jurist networks across South Asia to protect breastfeeding. (15th February 2023) - Sethi, Vani; Murira, Zivai
Abstract : In-country jurists remain an untapped resource for strengthening legal measures to support breastfeeding in South Asia, write Vani Sethi and Zivai Murira